Determination of Heavy Metals and Their Distribution In Different Size Fractionated Sediment Samples Using Different Analytical Techniques. Issue 3 (2nd April 2016) - Maity, Sukanta; Sahu, S. K.; Pandit, G. G.
Abstract: Distribution of heavy metals (Pb, Cu and Cd) in different size-fractionated sediment samples was studied using different analytical techniques such as flame atomic absorption spectrometry (FAAS), inductively coupled plasma atomic emission spectrometry (ICP-AES) and differential pulse anodic stripping voltammetry (DPASV). Pb and Cu concentrations were found to have respective variations of 6.58% and 9.45% from FAAS, ICP-AES and DPASV analysis. Cadmium was detectable only by DPASV because of its lower abundance in different size fractions. The percentage distribution of total organic carbon (TOC) and heavy metals increased with decrease in particle size. Metal concentrations increase with increasing TOC content in different size-fractionated sediment samples studied. Although the smallest fractions (< 53 μm) of sediment contributed only 3.4–17.8%, they had the highest mean distribution factor of 1.08 for Pb, 1.04 for Cu and 1.06 for Cd, respectively. Pb, Cu and Cd were correlated positively with organic carbon content in the sediment samples.